Impact of environment, social and governance on investors’ investment decision in Malaysia - Wong, Jia Hui (2023)
The purpose of this study is aimed to understand the impact of environment, social and governance (ESG) to investor’s investment decisions in Malaysia. This study had applied quantitative approach which questionnaire to be distributed through several online platform and social media for data collection from Malaysia’s individual investors who had experienced in investment in Malaysia. A total of 201 effective and valid responses were collected for the data analysis. The findings of this study found out that most of the independent variables (IV) has a significant positive relationship with the dependent variable (DV) – ESG consideration in investment decision nevertheless, Social Aspect – Customer & Public (Factor S1) and Social Aspect – Product & Service (Factor S3) have significant negative relationship with investment decision of Malaysia’s individual investors. The limitation for this study is single source for data collection which there will be possibility occurs common method variance (CMV). Furthermore, the limitation for this research is convenient sampling technique. This sampling technique is faster, easier and convenience however, the quality for target respondents may not have the same chance to participate in this research.